Juridical construction of socio-ecological security: Indonesia’s vulnerability to climate change - Atika Sari Diah Apriani; Triatmodjo Marsudi; Purwanto Harry (BIO Web of Conferences)
As an archipelagic state, Indonesia is very vulnerable to losing part of its land and islands due to climate change. Climate change causes atmospheric instability and sea level rise. Sea level rise that causes land loss, ecosystem damage, infrastructure damage, and even massive population displacement, are the impacts of climate change that affect environmental security. At the United Nations Framework Convention on Climate Change (UNFCCC) in 1992, the goal was to stabilize greenhouse gas concentrations to prevent harmful anthropogenic disturbances to the climate system. Therefore, as a response to overcoming the problem of the effectiveness of international environmental law, the idea of juridical construction in the protection of socio-ecological security is needed. Initiatives that can be undertaken by the government include the development of resilient infrastructure systems and land-use planning, as well as the restructuring of spatial planning, particularly for coastal areas and sensitive ecosystems. This research is a normative study that examines the legal framework of socio-ecological security concerning Indonesia’s vulnerability as an archipelagic nation due to the impacts of climate change. This research adopted a normative methodology with legislative and conceptual approaches.